Phenolic Compounds in Agro-Industrial Waste of Mango Fruit: Impact on Health and Its Prebiotic Effect – a Review - Mayra Nicolás García; Anahí Jobeth Borrás Enríquez; Jorge Luis González Escobar; Oscar de Jesús Calva Cruz; Viridiana Pérez Pérez; Mayra Sánchez Becerril (Polish Journal of Food and Nutrition Sciences)
The fruit processing industry generates huge amounts of waste annually, causing severe environmental problems. Mango processing produces around 20 million tons of wastes from the non-consumed fraction, mainly peels and seeds, which constitute 30–60% of the fruit weight. However, various phytochemicals found in these residues have been implicated in preventing cancer and also cardio-metabolic and gastrointestinal diseases. Particularly, phenolic compounds hold a promising potential to be utilized as modulatory agents of the human gut microbiota (prebiotics-like actions). This review article mainly discusses the effect of phenolics from mango wastes on gut microbiota modulation and its beneficial repercussions for human health. Moreover, it also discusses the importance of phenolic compounds of mango peel and seed kernel residues, their extraction, identification, and quantification.